Analisis Yuridis terhadap Pengrusakan Barang Milik Orang Lain Tanpa Disengaja Menurut Hukum Perdata dan Pidana - Delzanty, Kayla; Talitha, Raisyha; Hakim, Mohammad Akmal Taris; Rosdiana, Hani; Ramadhani, Sherlyta; Yuli, Yuliana (Media Hukum Indonesia (MHI), 2024)
Damaging other people's property is behavior that invites concern and worry in society. This action not only harms individual rights and interests, but also has broad social impacts. The material losses that arise can have an impact on the economic stability of a person or even a community. Apart from that, there are psychological aspects that also have an influence, such as feelings of insecurity and loss of trust in the surrounding environment. Therefore, legal regulations in both the criminal and civil realms have formulated strict provisions regarding this matter. In the realm of criminal law, destroying property can be considered a criminal act that can be subject to sanctions in the form of imprisonment or a fine, depending on the severity of the act and the value of the loss caused. Meanwhile, in the realm of civil law, damage to goods can be a basis for the owner of the goods to demand compensation for the losses suffered. The debate around how to confront and deal with damage to other people's property from a criminal and civil law perspective is becoming increasingly important in the context of justice and the protection of society.